Uji Empiris Mekanisme Transmisi Kebijakan Moneter: Interest Rate Pass-through Sektor Perbankan Indonesia - Wibowo, Buddi; Lazuardi, Eduardo (UI Scholars Hub, 2016)
Robust measurement of interest rates speed of adjustment to monetary policy changes is very important to obtain a comprehensive understanding on the monetary transmission process and the effectiveness of monetary policy. The speed of adjustment are determined by number of frictions that interfere with the transmission of monetary policy. We measure Indonesia interest rate pass-through which have distinct characteristics in terms of banking competition, segmented banking market and concentrated structure. Interest rate pass-through is measured by using Vector Error Correction Model (VECM) and Mean Adjusted Lags (MAL). This paper shows the interest rate adjustment did take a relatively long time.